APPRAISAL OF THE IMPLEMENTATION OF COMPUTER STUDIES CURRICULUM IN UPPER BASIC EDUCATION SCHOOLS IN ANAMBRA STATE (UNIZIK Journal of STM Education, 2024)
The Study appraised the implementation of Computer Studies Curriculum in Anambra State. Descriptive survey research design was used for the study. The population of this study comprised 310 computer/ICT teachers and 5753 UBE2 students. The sample size for the study comprised 34 Computer Studies teachers and 574 UBE students obtained through multi-stage sampling procedure. Data were collected using ‘Adequacy of Teachers for the Implementation of Computer Studies Checklist (ADTICSC), questionnaire on ‘Computer Studies Teachers’ Qualification Questionnaire’ (CSTQQ)’ and Classroom Observation Schedule (COS). The instrument was validated by three experts its reliability was established using Kuder-Richardson-20 formular. Coefficient values of 0.86 and 0.80 were obtained2 which was considered high enough to confirm the instrument as reliable. Data were analyzed using frequency counts, percentages and means. The findings revealed that majority of the sampled schools do not have adequate Computer Studies teachers for the implementation of Computer Studies curriculum. The finding of the study also revealed Computer Studies teachers are qualified for the implementation of Computer Studies curriculum and that lecture method was the most utilized teaching method for the implementation of Computer Studies curriculum and that computer studies teachers are adequate. It was concluded that implementation of Computer Studies Curriculum in Upper Basic Education schools is done to a low extent. It was recommended among others that government should provide the schools with adequate computer studies teacher for effective implementation of the computer studies curriculum.
Keywords: curriculum, curriculum implementation, computer studies